On the 2011 Outburst of the Recurrent Nova T Pyxidis - L. Izzo; M. della Valle; A. Ederoclite; M. Henze (Acta Polytechnica CTU Proceedings)
We discuss the nebular phase emission during the 2011 outburst of the recurrent nova T Pyxidis and present preliminaryresults on the analysis of the line profiles. We also present some discussions about the binary system configurations and the X-ray emission, showing that the white dwarf mass should be larger than 0.8 MΘ.